Child sexual abuse in Japan: A systematic review and future directions. (April 2017) - Tanaka, Masako; Suzuki, Yumi E.; Aoyama, Ikuko; Takaoka, Kota; MacMillan, Harriet L.
Abstract: Introduction: Estimating the national prevalence of child sexual abuse (CSA) and its association with health and developmental outcomes is the first step in developing prevention strategies. While such data are available from many countries, less is known about the epidemiology of CSA in Japan. Methods: For this systematic review, we searched English databases: Embase, Ovid MEDLINE(R) In-Process & Other Non-Indexed Citations, Ovid MEDLINE(R) Daily and Ovid MEDLINE(R), Ovid OLDMEDLINE(R), PsycINFO, and Japanese databases: Cinii, J-Stage, Children's Rainbow Center Japan, Japan Child and Family Research Institute, Japanese Journal of Child Abuse and Neglect to identify articles published before July 2015 examining the lifetime prevalence of CSA in Japan using non-clinical samples. Data were extracted from published reports. Results: We initially identified 606 citations and after abstract review, retrieved 120 publications. Six studies that met the selection criteria and additional two relevant studies were reviewed. The range of contact CSA for females was 10.4%–60.7%, and the prevalence of this type of CSA for males was 4.1%. The range of penetrative CSA for females was 1.3%–8.3% and that for males was 0.5%–1.3%. A number of methodological issues were identified, including a lack of validated measures of CSA, and low response rates. Conclusion: In contrast to a lower prevalence of penetrative CSA, the prevalence of contact CSA among Japanese females may be comparable or higher in relation to international estimates. Future research on children's perceptions of and exposure to sexual abuse, crime and exploitation in Japan is discussed.